2021
DOI: 10.2749/christchurch.2021.0293
|View full text |Cite
|
Sign up to set email alerts
|

On the potential for using bridge natural frequencies to detect scour: an experimental study

Abstract: <p>Monitoring bridges for precursors of failure has the potential to improve their safety and resilience. However, the most prominent cause of bridge failure, scour, is difficult to monitor as it occurs underwater. The potential to identify scour by monitoring changes in the natural frequencies of a bridge is studied experimentally in this research. A field study was carried out on a bridge with pre- existing scour confined to a section of a piled pier foundation, which was monitored throughout a repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The use of natural frequency to detect bridge pier integrity has been reported in Japanese railway bridges [19], although it has not been widely adopted in other parts of the world. A recent field deployment of this technique on a reinforced concrete road bridge indicated that the measurement error in natural frequency derived using ambient vibration data can be high, compared to the expected sensitivity of natural frequency changes due to scour [20][21][22]; therefore, it is important to experimentally establish the natural frequency sensitivity to scour of different bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural frequency to detect bridge pier integrity has been reported in Japanese railway bridges [19], although it has not been widely adopted in other parts of the world. A recent field deployment of this technique on a reinforced concrete road bridge indicated that the measurement error in natural frequency derived using ambient vibration data can be high, compared to the expected sensitivity of natural frequency changes due to scour [20][21][22]; therefore, it is important to experimentally establish the natural frequency sensitivity to scour of different bridges.…”
Section: Introductionmentioning
confidence: 99%